THE IMPLEMENTATION OF EMPLOYEE’S PERFORMANCE ASSESSMENT POLICY BASED ON GOVERNMENT REGULATION NO. 46 YEAR 2011 THROUGH THE IMPROVEMENT OF APPARATUS COMPETENCY IN TRAINING AND EDUCATION INSTITUTION IN CENTRAL JAVA PROVINCE (Universitas Negeri Semarang, 2014)
For improving the accountability of public sector performance, government is challenged to make an accountability system based on performing by creating the effective performing management model. The pressure of public sector organization, especially government organization either central or district and also government’s company and other public sectors for fixing their performances pushes to the building of public sector management organizational system based on performance-based management. This change is done for implementing the bureaucracy’s role and function exactly, quickly, and consistently for getting the utilization based on the constitution’s mandate. The bureaucracy’s reformation is expected to change the mind of the civil public servants from want to be served to be the servant (guardian) that makes the society happy. From relaxing culture, laziness, and undisciplined to be the hard-working culture, be spirit, innovative, creative, and discipline. In implementing the advising of civil public servant based on the performance achievement and career system through the working performance achievement, working performance is needed to be assessed. This is based on what is being mandated by the law no. 46 year 2011 about civil public servants’ working performance assessment. By doing this, they can serve appropriately like the expected competency.